The Call of the Church in Poverty Liberation: A Theological Study of the Existence of the Church Fighting for the Poor - Sitorus, Dasvan Abdi Natanael; Sitanggang, Pintor Marihot (Jurnal Penelitian Medan Agama, 2025)
The church involved in the struggle for the liberation of the poor should not only be thought of in terms of economic, political and cultural involvement, but should point first and foremost to the identity of the church as a sign of the Kingdom of God. The church's solidarity with the poor is based on the life of Christ who became poor with the poor in order to liberate them. The poverty of the church is a way of living the gospel message, namely the proclamation of the kingdom of life, justice, and reconciliation for the lowly and oppressed. The purpose of this study is to examine how the church can act as an agent of liberation according to the concept of Gustavo Gutierrez's theology of liberation. This study also aims to raise awareness among churches and congregations about the importance of the church's role in overcoming poverty, and to promote a deeper understanding of the relationship between liberation theology and the church's social responsibility. This article will explain how Christianity views poverty from a biblical perspective, then how Christian theology affirms the church's calling in the liberation of poverty. As part of the concrete form of church service in the liberation of poverty, this article explains the form of contextualization of church service in fighting for the liberation of poverty in the midst of society.